Revisionary and natural history notes on some species of the genus Gnamptogenys ROGER, 1863 (Hymenoptera: Formicidae) - Delsinne, T. (2016)
Taxonomic clarifications and natural history data dealing with some species of the genus Gnamptogenys are offered: Gnamptogenys bufonis (MANN, 1926) is synonymized under G. simulans (EMERY, 1896); G. vriesi BRANDO & LATTKE, 1990 is redescribed and illustrated with SEM and montage images, the peculiar morphology of its compound eye is discussed. Also, an updated key for the G. minuta group species is presented and a nest of G. minuta (EMERY, 1896) is described. The species known up to now as G. costata (EMERY, 1889) is renamed G. coxalis (F. SMITH, 1857), and the species misidentified up to now as G. coxalis (ROGER, 1860) is renamed G. Sinhala LATTKE sp.n.